Phonological analysis of English consonants pronunciation - Ambalegin Ambalegin (English, 2021)
This is descriptive qualitative research phonologically investigating the English consonant sounds as the central phenomena represented by letters. The theories of Bauer, Hayes, Katamba, Kreidler, McMahon, and Yule were applied in this research. The method of data collection was an observational method. The articulatory phonetic identity method was a method in analyzing the data with competence in differentiating technique. The Oxford Advanced Learner’s Dictionary as a standard form of British pronunciation was a tool to compare the sound produced and differentiate the English Alphabet letter. There are some patterns of English consonant pronunciation. Letters p, s, t, c, ɡ (gh- close syllable) meet h will produce fricative. Letter r is equivowel at the r-close syllable. Letter n meets /k/ will produce /ŋ/. Letter t is pronounced as /ʃ/ in morpheme noun form -tion. Letter s is pronounced as /ʃ/ in morpheme noun form –(s)sion. Letter t is pronounced as /tʃ/ in the final syllable -ture. Letter s is pronounced as /ʒ/ in the final syllable -sure. Letter s is pronounced as /ʒ/ in morpheme noun form –(s)ion. In -ue close syllable, -ue is not pronounced.